2011
DOI: 10.1037/a0022983
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of posttraumatic stress disorder in men who sustain intimate partner violence: A study of helpseeking and community samples.

Abstract: Extensive work has documented an association between sustaining intimate partner violence (IPV) and posttraumatic stress disorder (PTSD) among women, yet little research has documented the same association in men, even though men comprise 25–50% of all IPV victims in a given year. Previous studies also show that women who sustain intimate terrorism (IT), a form of IPV that is characterized by much violence and controlling behavior, are at even greater risk for PTSD than women who sustain common couple violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 64 publications
7
82
0
2
Order By: Relevance
“…In fact, the frequency with which men sustained violence in the previous year (46.7 acts) was comparable to the frequency of violence sustained in samples of battered women (between 15 and 68 acts per year; Giles-Sims, 1983;Johnson, 2006;Okun, 1986;Straus, 1990). In addition, their rates of PTSD (Hines & Douglas, 2011) were also similar to samples of battered women (Golding, 1999).…”
Section: Male Victims Of Severe Partner Violencementioning
confidence: 73%
See 1 more Smart Citation
“…In fact, the frequency with which men sustained violence in the previous year (46.7 acts) was comparable to the frequency of violence sustained in samples of battered women (between 15 and 68 acts per year; Giles-Sims, 1983;Johnson, 2006;Okun, 1986;Straus, 1990). In addition, their rates of PTSD (Hines & Douglas, 2011) were also similar to samples of battered women (Golding, 1999).…”
Section: Male Victims Of Severe Partner Violencementioning
confidence: 73%
“…Participants indicate on a 5-point scale (1 = not at all, 5 = extremely) the extent to which they were bothered by each symptom in the previous month. The PCL has been used to evaluate PTSD symptomatology in a variety of populations, including female sexual assault victims (Blanchard, Jones-Alexander, Buckley, & Forneris, 1996) and male victims of IPV (Hines & Douglas, 2011). The PCL has demonstrated excellent reliability, with alpha coefficients above .90 (Blanchard et al, 1996;Lang, Laffaye, Satz, Dresselhaus, & Stein, 2003;Weathers et al, 1993) and test-retest reliability of .96 (Weathers et al, 1993).…”
Section: Post-traumatic Stress Disorder Symptomsmentioning
confidence: 99%
“…104 Although the majority of PIPV research has focused primarily on women, 105 it was found that men also experience mental health problems associated with PIPV. 103,106 It is estimated that more than half of PIPV events are not reported to the police, 107 suggesting the need for intervention efforts aimed outside the realm of law enforcement. Healthcare providers, particularly those working within ED settings, can serve as an important point of contact for victims of PIPV.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, Brownridge (2010) found that both types of IPV were found equally within both types of relationship and actually cohabiting couples had higher odds of experiencing both. Furthermore, Anderson (2008) These studies have included those comparing prevalence of both types of effects amongst men and women (e.g., Hines & Saudino, 2003); associations with binge drinking (Hines & Straus, 2007); qualitative analysis of callers to a domestic abuse help line for men ; associations with personality and personality disorders (e.g., Hines, 2008;Hines & Saudino, 2008) and with posttraumatic stress disorder (e.g., Hines & Douglas, 2011). All of these studies have suggested that men suffer psychological and physical effects of IPV victimization.…”
mentioning
confidence: 99%